Utilizing unmanned aerial vehicles (UAVs) for real-time insect surveillance in precision Integrated Pest Management systems - Mir, Sajad Hussain; Ahmed, Mohammad Jamal; G S, Anjana; Hydari, Asgar Ali; Reyaz, Rafiya (Indian Journal of Plant Protection, 2025)
Unmanned Aerial Vehicles (UAVs) play a pivotal role in revolutionizing precision integrated pest management (IPM) by providing a sophisticated and efficient means of monitoring insects. Equippedwith advanced sensors and imaging technology, UAVs can capture high-resolution aerial data, enabling real-time identification and analysis of insect populations across agricultural landscapes. This proactive approach allows for timely interventions, optimizing pest control strategies and minimizing the use of pesticides. The ability of UAVs to cover vast areas quickly enhances the overall effectiveness of IPM, contributing to sustainable and environmentally conscious farming practices. UAVs play a significant role in precision insect monitoring and management, fostering more targeted and resource-efficient pest control in agriculture. UAVs facilitate the collection of multispectral and thermal data, aiding in the detection of subtle changes in plant health caused by insect infestations. This information helps farmers identify affected areas early on, enabling them to implement precise interventions. The integration of machine learning algorithms further enhances UAV capabilities by automating insect recognition processes, allowing for swift and accurate identification of pest species. UAVs provide a cost-effective alternative to traditional methods of insect monitoring, reducing the need for labour-intensive fieldwork. Overall, the utilization of unmanned aerial vehicles in insect monitoring for precision IPM signifies a technological leap towards sustainable agriculture practices with minimized environmental impact and increased crop yield.